A Conceptual Model to Examine the Relationship between "Internal Marketing" and "Market Orientation" Considering the Mediator Variables of "Organizational Commitment" and "Organizational Citizenship Behavior: A Case Study in Bank Mellat - Tahmores Hasangholipor Yasory; Manochehr Ansari; Akram Elahi Gol Elahi Gol (‫مدیریت بازرگانی, 2012)
The purpose of this paper is to examine the relationship between "internal marketing" and "market orientation" considering the mediator variables of "Organizational Commitment" and "Organizational Citizenship Behavior" in Bank Mellat in Tehran City branches as a financial-service provider company. The questionnaire in this study was taken from the related literature; its validity was tested by the field experts as well as by factor analysis. The research methodology adopted in this study is descriptive and of corelational type and data was analyzed using Structural Equation Model. Research population consisted of Bank Mellat employees throughout Tehran. A sample of 323 employees was chosen by Cluster sampling and finally 261 questionnaires were gathered. Findings of this study show that there are positive correlation between Internal marketing and Market Orientation considering the mediator variable of "Organizational Commitment" in Bank Mellat Tehran.